Four-point one-loop amplitude computation in the pure spinor formalism - Mafra, Carlos R. [UNESP] (Springer Nature, 2006)
The massless 4-point one-loop amplitude computation in the pure spinor formalism is shown to agree with the computation in the RNS formalism. © SISSA 2006.
Keywords: Field Theories in Higher Dimensions; Superstrings and Heterotic Strings